Transcriptome-Wide m6A Analysis Provides Novel Insights Into Testicular Development and Spermatogenesis in Xia-Nan Cattle - Liu, Shen-he; Ma, Xiao-ya; Yue, Ting-ting; Wang, Zi-chen; Qi, Kun-long; Li, Ji-chao; Lin, Feng; Rushdi, Hossam E.; Gao, Yu-yang; Fu, Tong; Li, Ming; Gao, Teng-yun; et al. (Frontiers in Cell and Developmental Biology, 2021)
Testis is the primary organ of the male reproductive tract in mammals that plays a substantial role in spermatogenesis. Improvement of our knowledge regarding the molecular mechanisms in testicular development and spermatogenesis will be reflected in producing spermatozoa of superior fertility. Evidence showed that N6-Methyladenosine (m6A) plays a dynamic role in post-transcription gene expression regulation and is strongly associated with production traits. However, the role of m6A in bovine testis has not been investigated yet. In this study, we conducted MeRIP-Seq analysis to explore the expression profiles of the m6A and its potential mechanism underlying spermatogenesis in nine bovine testes at three developmental stages (prepuberty, puberty and postpuberty). The experimental animals with triplicate in each stage were chosen based on their semen volume and sperm motility except for the prepuberty bulls and used for testes collection. By applying MeRIP-Seq analysis, a total of 8,774 m6A peaks and 6,206 m6A genes among the studied groups were identified. All the detected peaks were found to be mainly enriched in the coding region and 3′- untranslated regions. The cross-analysis of m6A and mRNA expression exhibited 502 genes with concomitant changes in the mRNA expression and m6A modification. Notably, 30 candidate genes were located in the largest network of protein-protein interactions. Interestingly, four key node genes (PLK4, PTEN, EGR1, and PSME4) were associated with the regulation of mammal testis development and spermatogenesis. This study is the first to present a map of RNA m6A modification in bovine testes at distinct ages, and provides new insights into m6A topology and related molecular mechanisms underlying bovine spermatogenesis, and establishes a basis for further studies on spermatogenesis in mammals.